VD_FINDINFO ML / 2011 / 28 vom 4. August 2008 - VD Tribunal cantonal (2008)
MAINLEVÉE DÉFINITIVE, TITRE EXÉCUTOIRE, DÉPENS, DÉCLARATION D'EXÉCUTION, SOLIDARITÉ | 1 al. 2 ch. 1 CL, 86 LDIP, 70 al. 2 LP, 80 LP